Laboratory assessment of pavement foundation materials - Cheung, Lam Wah (1994)
The main aim of this research was to improve laboratory test methods for describing pavement foundation materials so that analytical design based on appropriate mechanical parameters of materials could be performed in practice. The study started by assessing the relevance of currently available methods to describe materials in pavement foundations and reviewing factors influencing the responses of these materials to repeated loading.